A New Transfer Technique for Graphene Deposited by CVD on Metal Thin Films. Issue 1658 (22nd May 2014) - Amato, G.; Simonetto, E.; Croin, L.; Vittone, E.
ABSTRACT: Chemical Vapor Deposition of graphene on metallic substrates is one of the most attracting techniques for large area graphene production. The technique widely employed for transferring graphene to other substrates involves deposition of a polymer support with subsequent etching of the metal substrate. Here we report a safer transfer process, which requires a two-step PMMA deposition and bonding under pressure. Sheets of graphene before and after transfer have been both characterized by Raman spectroscopy, and show comparable quality, indicating that the proposed technique does not introduce additional defects in graphene.